Estudo experimental da perda de circulação de fluidos não newtonianos em meios porosos fraturados - Schneider, Cássio Luís (2019)
Studies involving the flow of non-newtonian fluids into totally or partially porous ducts or channels have received considerable attention because of their wide range of engineering applications such as drilling, production and recovery of oil and gas reservoirs. In the drilling process the lost circulation is one of the main phenomena that interfere with the well operation. The presence of fractures, common in all well-formation, added to the pressure gradient, significantly enhances fluid loss. In the present work, the flow of non-newtonian fluid in a partially porous and fractured channel is investigated, characterizing the lost circulation phenomenon. The tests presented were performed in an experimental set-up, comprising a rectangular test section, representing a wellformation with a transverse fracture, instrumented with pressure gauges, flow and temperature monitors. Aqueous solutions of carbopol, xanthan gum, carboxymethyl cellulose and glycerin were used as working fluids and crosslinked foam ceramic filters to represent the rock formation. In order to evaluate the variation influence of parameters of the flow, fluid and porous medium, the Reynolds number of the flow, the flow rate at the fracture, the viscosity of the fluid, the working fluid and the cell opening of the porous medium were varied. The results show that all parameters are capable of altering the pressure settings during the lost circulation, exerting a direct influence on the pressure gradient generated between the channel and the fracture.